Trends in smoking-related diseases by socioeconomic position following a national smoking ban in 2007: a nationwide study in the Danish population - Nanna Schneekloth Jarlstrup; Lau C. Thygesen; Charlotta Pisinger; Jørgen Vestbo; Morten Grønbæk; Janne S. Tolstrup (BMC, 2023)
Abstract Background National comprehensive smoke-free legislation has been found to decrease the incidence of several smoking-related diseases. In 2007, Denmark introduced a national smoking ban, which banned smoking indoor in workplaces and public places, although only partial restrictions were applied in certain settings. We examined the impact of the smoking ban on smoking-related diseases and whether this differed across socioeconomic groups. Methods Interrupted time series analyses of nationwide register data were performed using Poisson regression models to examine the differential impact of the smoking ban on monthly incidence rates of acute myocardial infarction, chronic obstructive pulmonary disease, and smoking-related cancers from 2002 to 2015. Immediate changes in incidence rates after the smoking ban and long-term changes in disease trends were estimated by comparing data from the pre- and post-ban period. Models were stratified by socioeconomic position. Results Overall, we found neither immediate changes in rates of acute myocardial infarction, chronic obstructive pulmonary disease, and smoking-related cancers following the smoking ban nor long-term post-ban changes in disease trends as compared to before the ban. Results did not differ across socioeconomic groups. A pronounced socioeconomic gradient in incidence rates was observed for all outcomes both before and after the smoking ban. Conclusion The national smoking ban was not associated with a lower incidence of smoking-related diseases in the post-ban period compared to pre-ban levels and no differences between socioeconomic groups were observed. Future tobacco control in Denmark should consider which measures most effectively target the low socioeconomic groups to decrease the current strong socioeconomic inequality in health.